휘발유 승용자동차의 엔진 배기량이 실도로 주행시 이산화탄소 및 질소산화물 배출에 미치는 영향 - 이종태; Jongtae Lee; 김형준; Hyung Jun Kim; 임윤성; Yun Sung Lim; 윤창완; Chang Wan Yun; 길지훈; Ji Hoon Keel; 홍유덕; You Deug Hong (한국분무공학회지, 2018)
Recently, registrated passenger cars have increased and were close about seventy million at the end 2017 year in Korea. Among the passenger car using gasoline fuel make up forty six percentage of total registrated vehicles. In this study, investigation on real driving emission characteristics in the passenger car using gasoline fuel with various engine displacements were carried out. The real driving emission characteristics were measured and analyzed by using PEMS (Portable Emission Measurement System). PEMS was composed of gas analyzer, emission flow meter and sample conditioning system et al. Also, test six vehicles were selected to the gasoline passenger car with engine displacement from 1.6L to 3.7L. Two test routes with engine start of cold and hot conditions were applied to analyze the emission characteristics of RDE, respectively. The results show that the CO 2 emission have a increasing trend as the engine displacement and vehicle weight. Also, it is guessed that the CO 2 emission and vehicle weight were more correlated than the engine displacements. On the other hand, NOx emissions of RDE have not increasing or decreasing tendency according engine displacements or vehicle weight because the activation of three-way catalyst in the gasoline vehicles.